The Rise of Exclusive Boarding Houses: Gentrifying Kampung Through New Wave of Urbanization in Jakarta - Dwiyanti Kusumaningrum; Jalu Lintang Yogiswara Anuraga; Tria Anggita Hafsari (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2020)
This study discusses gentrification in Kampung Paseban caused by the urbanization of Jakarta. The aim of this study is to show how urban processes create gentrification in kampung, focusing on the rise of exclusive boarding houses and its consequence on social changes within Kampung Paseban in Central Jakarta. The analysis employs a qualitative approach that emphasizes the interpretation of the spatial and urban social changes in Kampung Paseban. The method consists of literature review, spatial mapping, in-depth interviews, and field observations. This study shows that the rise of exclusive boarding houses followed by the influx of middle-class migrants has created dualism in both the physical and social aspects of the kampung. The old kampung vibe in Kampung Paseban has now diminished and has been replaced by the emergence of exclusive boarding houses which has become ubiquitous since the 2000's. Gentrification has created a competitive environment in the local economy which causes struggles for the natives and the settlers. In terms of sociocultural impact, the existence of exclusive boarding houses that provide a more private space and are disconnected from the surrounding environment causes social interaction to become more less between the newcomers and the natives. This study shows how kampung copes with urban situations; creating a new social environment, which demonstrates urbanism within kampung.